Cdk5 phosphorylates Cdh1 and modulates cyclin B1 stability in excitotoxicity - Maestre, Carolina (Nature Publishing Group, 2008)
Anaphase-promoting complex/cyclosome (APC/C), an E3 ubiquitin ligase that destabilizes cell cycle proteins, is activated by Cdh1 in post-mitotic neurons, where it regulates axonal growth, synaptic plasticity and survival. The APC/C–Cdh1 substrate, cyclin B1, has been found to accumulate in degenerating brain areas in Alzheimer's disease and stroke. This highlights the importance of elucidating cyclin B1 regulation by APC/C–Cdh1 in neurons under stress conditions relevant to neurological disease. Here, we report that stimulation of N-methyl-D-aspartate receptors (NMDARs) that occurs in neurodegenerative diseases promoted the accumulation of cyclin B1 in the nuclei of cortical neurons; this led the neurons to undergo apoptotic death. Moreover, we found that the Ser-40, Thr-121 and Ser-163 triple phosphorylation of Cdh1 by the cyclin-dependent kinase-5 (Cdk5)–p25 complex was necessary and sufficient for cyclin B1 stabilization and apoptotic death after NMDAR stimulation. These results reveal Cdh1 as a novel Cdk5 substrate that mediates cyclin B1 neuronal accumulation in excitotoxicity.